2022
DOI: 10.3389/fchem.2022.863364
|View full text |Cite
|
Sign up to set email alerts
|

Exosomes Derived From Human Gingival Mesenchymal Stem Cells Attenuate the Inflammatory Response in Periodontal Ligament Stem Cells

Abstract: This study aimed to explore the effects of exosomes derived from human gingival mesenchymal stem cells (GMSC-Exo) on the inflammatory response of periodontal ligament stem cells (PDLSCs) in an inflammatory microenvironment in order to restore the regenerative potential of PDLSCs, which promotes periodontal tissue regeneration in patients with periodontitis. Periodontitis is a chronic infectious disease characterized by periodontal tissue inflammation and alveolar bone destruction. PDLSCs are regarded as promis… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
10
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 20 publications
(14 citation statements)
references
References 63 publications
1
10
0
Order By: Relevance
“…These results are consistent with our observations. Our previous studies have indicated that GMSC‐Exo can down‐regulate Wnt5a expression in the inflammatory microenvironment (Sun et al, 2022). Wnt5a is a vital factor in the non‐classical Wnt pathway and is also highly expressed in periodontal inflammatory microenvironments (Sun et al, 2022).…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…These results are consistent with our observations. Our previous studies have indicated that GMSC‐Exo can down‐regulate Wnt5a expression in the inflammatory microenvironment (Sun et al, 2022). Wnt5a is a vital factor in the non‐classical Wnt pathway and is also highly expressed in periodontal inflammatory microenvironments (Sun et al, 2022).…”
Section: Discussionmentioning
confidence: 99%
“…Our previous studies have indicated that GMSC‐Exo can down‐regulate Wnt5a expression in the inflammatory microenvironment (Sun et al, 2022). Wnt5a is a vital factor in the non‐classical Wnt pathway and is also highly expressed in periodontal inflammatory microenvironments (Sun et al, 2022). It has been shown that the non‐classical Wnt pathway engages in crosstalk with the classical Wnt signalling pathway in the inflammatory microenvironment and jointly regulates the osteogenic differentiation of PDLSCs (Liu et al, 2011).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Flow cytometric analysis revealed positive expressions for the surface markers CD29, CD73, and CD90 and the negative expression of CD45 (Figure 2E–H). 28 …”
Section: Resultsmentioning
confidence: 99%
“…EVs inherit the function of their parent cells and have lower immunogenicity; therefore, they play important roles in immune regulation and tissue regeneration [ 106 ]. For example, EVs derived from human GMSCs (GMSC-EVs) could inhibit the inflammatory response of PDLSCs by regulating the expression of NF-κB signaling and Wnt5a, which restored the regenerative potential of PDLSCs and promoted periodontal tissue regeneration in patients with periodontitis [ 107 ].…”
Section: Evs In Pulp Regenerationmentioning
confidence: 99%